An Architecture for Proof Planning Systems - Dennis, Louise Abigail (IJCAI Inc, 2005)
This paper presents a generic architecture for proof planning systems in terms of an interaction between a customisable proof module and search module. These refer to both global and local information contained in reasoning states.